On a class of Caputo modified fractional differential equations with advanced arguments - Derhab, Mohammed (Jordan Journal of Mathematics and Statistics, 2025)
In this paper by using Banach’s contraction principle, we prove the existence and uniqueness of solutions for a class of fractional differential equations with advanced arguments has a unique solution. Moreover, we give several examples illustrating the application of our results.